Age and cellular composition influence overall survival in a collective of non-immunocompromised patients with EBV-positive diffuse large B-cell lymphoma from a German lymphoma center. - Johrens, K.; Trappe, R. U.; Lenze, D.; Pfreundschuh, M.; Ziepert, M.; Hummel, M.; Anagnostopoulos, I. (Leuk Lymphoma, 2016)
We investigated 41 diffuse large B-cell lymphomas (DLBCL) diagnosed at one center harboring >/=50% of latently Epstein-Barr virus (EBV)-infected neoplastic cells occurring in 34 patients aged >/=50 years and in 7 patients younger than 50 years in the absence of any known immunodeficiency for the expression patterns of EBV latent and immediate-early proteins, for the differentiation stage of the neoplastic cells, the presence of cytogenetic alterations and a possible co-infection with the human herpes virus (HHV)-8. Here, we show that EBV-positive DLBCLs rarely arise from naive and more frequently from post-germinal center B-cells that often contain crippling immunoglobulin gene mutations. Most of the lymphomas did not exhibit breaks in the BCL2, BCL6, and MYC genes and none of the cases investigated contained HHV-8 sequences. Patients aged <50 years performed better than older ones while in patients aged >/=50 years only the cellular composition had an impact on overall survival.
Keywords: Adult; Age Factors; Aged; Biomarkers; Epstein-Barr Virus Infections/*complications/virology; Female; Gene Rearrangement, B-Lymphocyte; Genes, Immunoglobulin; Germinal Center/pathology; *Herpesvirus 4, Human/genetics; Humans; Immunohistochemistry; Immunophenotyping; In Situ Hybridization, Fluorescence; Kaplan-Meier Estimate; Lymphoma, Large B-Cell, Diffuse/*etiology/*mortality/pathology; Male; Middle Aged; Proportional Hazards Models